New Libraries in Old Buildings : Creative Reuse - Hauke, Petra; Niess, Robert; Latimer, Karen (2021)
This book focuses on difficulties and opportunities in revitalization of old, derelict or abandoned buildings into a library and investigates the transformation of buildings which originally had a different purpose. The publication shows worldwide best practice examples from different types of libraries in historic environments, both urban and rural, while maintaining a focus on sustainability concerning the architecture and interior design.